2014
DOI: 10.1371/journal.pone.0093263
|View full text |Cite
|
Sign up to set email alerts
|

Impulsive Choice Predicts Poor Working Memory in Male Rats

Abstract: A number of maladaptive behaviors and poor health outcomes (e.g., substance abuse, obesity) correlate with impulsive choice, which describes the tendency to prefer smaller, immediate rewards in lieu of larger, delayed rewards. Working memory deficits are often reported in those diagnosed with the same maladaptive behaviors. Human studies suggest that impulsive choice is associated with working memory ability but, to date, only one study has explored the association between working memory and impulsive choice i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Trait impulsivity differences manifest in other behavioral domains (Hayward et al, 2016). For instance, it has been observed that HI animals perform worse in working memory tasks (James et al, 2007, Renda et al, 2014) and present increased anxiety-like behavior(Stein et al, 2015) though some conflicting evidence has also been reported (Velázquez-Sánchez et al, 2014). Furthermore, HI predicts nicotine and cocaine self-administration (Anker et al, 2009, Dalley et al, 2007, Diergaarde et al, 2008, Perry et al, 2008) and increases seeking behavior for sucrose and palatable food (Diergaarde et al, 2009, Velázquez-Sánchez et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Trait impulsivity differences manifest in other behavioral domains (Hayward et al, 2016). For instance, it has been observed that HI animals perform worse in working memory tasks (James et al, 2007, Renda et al, 2014) and present increased anxiety-like behavior(Stein et al, 2015) though some conflicting evidence has also been reported (Velázquez-Sánchez et al, 2014). Furthermore, HI predicts nicotine and cocaine self-administration (Anker et al, 2009, Dalley et al, 2007, Diergaarde et al, 2008, Perry et al, 2008) and increases seeking behavior for sucrose and palatable food (Diergaarde et al, 2009, Velázquez-Sánchez et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is that there is not a source of bias in our model. Bias could arise from impulsive responding (Matell and Portugal, 2007;Renda et al, 2014), for example. The model does not capture correctly the pressing rate distribution of rat 3, whose peak response lies 5 to 10 seconds delayed from the target time.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, individual differences in working memory correlate with differences in intertemporal choice (Shamosh et al, 2008), and explicit training in working memory performance reduces impulsive choice (Bickel, Yi, Landes, Hill, & Baxter, 2011). Experiments with rats replicate the correlational work, with subjects who chose larger, later options in a delay choice intertemporal choice task also performing well on an operant delayed matching-to-sample working memory task (Renda, Stein, & Madden, 2014). A study using a radial arm maze task to test working memory in rats, however, did not show a relationship between intertemporal choice and working memory (Dellu-Hagedorn & Dellu, 2006).…”
Section: Working Memorymentioning
confidence: 93%